(3GdGUGHGJ GdQjGVjI h WQb YdGLgGs - (3eMeO GbHGd QSeis ((3GdbGgQIs (3OGQ GdaLQ ddfTQ h ddJhRjYs, 2008)
(3Yde GdGUGHGJ ef Gge GdYdhe GdJj jhLO HgG jhejG cd LOjO h bO GKHJJ GdGHMGK GdYdejI GdLOjOI eOi GdJbOe aj Yde GdGUGHGJ ddQjGVjjf h GdYGeI, h gPGd GdcJGH GdPj Hjf GjOjfG jMJhj Ydi GZdH GdeYdheGJ aj Yde GUGHGJ GdQjGVjjf h WQb YdGLgG h GdhbGjI efgG hcPdc WQb GdYdGL GdWHjYj h GUGHGJ GdYXGe NGUI efgG cShQ h GGUGHGJ GdGWQGa GdSadi h GWdGdI Ydi GdefTWGJ h GdYbGbjQ GdeNOQI(B.s
Keywords: (3GdWH GdQjGVjs; (3GdYdGL GdWHjYjs